Exploring the Hidden World of Vectors of Chagas Disease: A Fascinating Look at the Taxonomic Aspects of the Psammolestes Genus (Hemiptera, Triatominae) - de Oliveira, Jader; Alevi, Kaio Cesar Chaboli; Almeida, Carlos Eduardo; Olaia, Nicoly [UNESP]; Cacini, Gustavo Lázari [UNESP]; Galvão, Cleber; Herrera, Heitor Miraglia; Santos, Filipe Martins; Rosa, João Aristeu da [UNESP] (MDPI, 2023)
Chagas disease (CD) is a neglected illness affecting approximately seven million individuals, with vector transmission occurring via triatomine bugs. The Rhodniini tribe comprises 24 species, grouped into the Rhodnius and Psammolestes genera. Given the importance of accurately identifying CD vectors, the taxonomy of Psammolestes spp. was revisited using morphological and morphometric data. Specimens of P. tertius, P. coreodes, and P. arthuri were collected, and the morphological characteristics of the head, thorax, abdomen, and eggs were analyzed. Morphometric studies of eggs were also conducted. Dichotomous keys allowing for the differentiation of Psammolestes spp. were elaborated based on adult insect and egg morphological characteristics. Through these studies, it was possible to differentiate the three Psammolestes species and confirm that this genus should not be classified under the Rhodnius genus, contributing to Rhodniini taxonomy.
Keywords: chagas disease vectors; Psammolestes arthuri; Psammolestes coreodes; Psammolestes tertius; Rhodniini